A study on meme propagation in multimemetic algorithms - Nogueras, Rafael; Cotta, Carlos (Zielona Góra: Uniwersytet Zielonogórski)
Multimemetic algorithms (MMAs) are a subclass of memetic algorithms in which memes are explicitly attached to genotypes and evolve alongside them. We analyze the propagation of memes in MMAs with a spatial structure. For this purpose we propose an idealized selecto-Lamarckian model that only features selection and local improvement, and study under which conditions good, high-potential memes can proliferate. We compare population models with panmictic and toroidal grid topologies.
Keywords: memetic algorithms; spatial structures; meme propagation